The Effect of Green Marketing on Customer Satisfaction - Stefanny Jonathan; Wiwik Nirmala Sari (CV. Syntax Corporation Indonesia, 2023)
The concept of environmentally friendly marketing has developed due to public awareness. This matter made many companies apply the green marketing concept in marketing their products to create customer satisfaction. Research was conducted with the aim of finding out The influence of green marketing on customer satisfaction. In the process of analysis, research A case study was conducted at Starbucks Coffee located at Bez Plaza. The location was selected because Starbucks Coffee is one of the first businesses to implement a green marketing system. The research method used is quantitative. The data collection process is carried out by distributing questionnaires to 243 visitors. In this research, it was concluded that green marketing has a significant effect on customer satisfaction.